The economywide impacts of increasing water security through policies on agricultural production: The case of rice and sugarcane in Pakistan - Davies, Stephen; Akram, Iqra; Ali, Muhammad Tahir; Hafeez, Mohsin; Ringler, Claudia (International Food Policy Research Institute, 2023)
Increasing demand for water juxtaposed with shrinking supplies will require a transfer of water resources out of agriculture into the domestic, industrial, and ideally environmental sectors. To examine the potential of policies to facilitate a release of water from agriculture, this paper uses IFPRI’s Computable General Equilibrium Model with a water extension, CGE-W, to assess the impact of commodity taxes on two highly water consumptive crops, rice and sugarcane, on water consumption and the overall economy. We find that land use grows by 1.56 million acres overall when the tax is imposed on both commodities, while 3.2-million-acre feet (MAF) of consumed water, equivalent to 6.35 MAF of water withdrawals, are released from agriculture. These outcomes are due to sugarcane’s reduced use of land over two cropping seasons and significant changes in cropping patterns. The study also examined releases of water from other possible policy measures and found that an even tax rate of 30% on sugarcane, rice and cotton yields 8.73 MAF of water from agriculture. However, with a hotter, drier climate virtually all these releases of water disappear because water must stay in agriculture due to higher evaporation and less precipitation, which raises irrigation demands. The needed policies will go beyond just taxation and might include changing cropping patterns and irrigation practices, as well as development of drought resistant varieties. Other approaches, such as buying tubewells from farmers, and developing markets for nonagricultural purchases of water, may have a role. The role of international trade in sugar and rice is shown to be significant and should be considered further in these analyses.